Prayer in the Gospels : a theological exegesis of the ideal pray-er - Nygaard, Mathias. (Biblical Interpretation Series, 2012)
In Prayer in the Gospels Mathias Nygaard offers a new reading of the prayer materials of the Gospels. The main focus is the theological anthropology of the prayer texts. This aspect is described through a text-centered analysis of the 'ideal pray-er', one aspect of the implied audiences. An emphasis on the responses elicited by the material in question gives religious experience a central role in the theological discussion. Nygaard argues that in the Gospels humans are defined by the gifts bestowed in Jesus Christ, and through the dialogical reception of those gifts in prayer. The result is a kenotic and irreducible understanding of a 'self' defined from without, as appropriate to the 'logic of the cross' and the eschatology of the texts.